2018
DOI: 10.4310/jsg.2018.v16.n4.a3
|View full text |Cite
|
Sign up to set email alerts
|

Invariants of Legendrian and transverse knots in monopole knot homology

Abstract: We use the contact invariant defined in [2] to construct a new invariant of Legendrian knots in Kronheimer and Mrowka's monopole knot homology theory (KHM ), following a prescription of Stipsicz and Vértesi. Our Legendrian invariant improves upon an earlier Legendrian invariant in KHM defined by the second author in several important respects. Most notably, ours is preserved by negative stabilization. This fact enables us to define a transverse knot invariant in KHM via Legendrian approximation. It also makes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The second author and Rutherford [35,Theorem 5.4] showed that if the ruling polynomial R Λ (z) has positive degree then Λ is A (2) -compatible. 1 The following result is similar but allows for R Λ (z) to be a constant as well.…”
Section: A (2)mentioning
confidence: 87%
See 3 more Smart Citations
“…The second author and Rutherford [35,Theorem 5.4] showed that if the ruling polynomial R Λ (z) has positive degree then Λ is A (2) -compatible. 1 The following result is similar but allows for R Λ (z) to be a constant as well.…”
Section: A (2)mentioning
confidence: 87%
“…There are infinitely many Legendrian knots Λ such that U ≺ Λ but Λ ≺ U . 1 The convention in [35] is that a ruling ρ with s switches and c right cusps contributes z s−c to the ruling polynomial, so their condition is deg RΛ(z) ≥ 0. We instead use the convention z s−c+1 of [40], so that the 2-graded and ungraded ruling polynomials match the appropriate coefficients of the HOMFLY-PT and Kauffman polynomials respectively.…”
Section: A (2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Given the existence of exact, non-orientable Lagrangian endocobordisms for a stabilized Legendrian, it is natural to ask: What Legendrian knots can appear as a "slice" of such an endocobordism? The parallel question for orientable Lagrangian endocobordisms has been studied in [9,4,12]. The non-orientable version of this question is closely tied to the question of whether non-orientable Lagrangian cobordisms define an equivalence relation on the set of Legendrian knots.…”
Section: Introductionmentioning
confidence: 99%